(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT The purpose of this study was to find out the horizontal career pattern, vertical career pattern and diagonal career pattern in the Agency for Personnel and Human Resources Development Jeneponto Regency. This study used phenomenological types to find out what problems occurred and the development of information and data acquisition was obtained by researchers during in-depth interviews. The results of this study indicated that the career pattern at the BKPSDM office in Jeneponto Regency had not run well, both from job mutation. Mutations according to position clumps, experience, rank, job training, as well as the expertise of a civil servant and in accordance with the Jeneponto Regent’s Regulations had not run properly. Horizontal career patterns in terms of shifting employees to the same position clump, some were appropriate, some were not appropriate, vertical career patterns in terms of rank and training for positions that had not been carried out properly due to the track record of employees and the positions occupied were not appropriate, and motivation or employee encouragement was not present in conducting education and training. While the diagonal career pattern in improving the skills of civil servants in occupying a position in order to improve the quality of employees because basically Civil Servants’ work should not refer to regulations. Keywords: Career Pattern, Civil Servant Position